Neonatal ECMO - Van Ommen, Cornelia Heleen; Neunert, Cindy E.; Chitlur, Meera B. (Frontiers in Medicine, 2018)
Extracorporeal membrane oxygenation (ECMO) is becoming increasingly utilized to manage neonates with cardiac and respiratory failure. The procedure involves extensive anticoagulation in a sick neonate with underlying disease pathology. In addition, the immature hemostatic system in the neonate adds to the complexity of titrating the necessary anticoagulation. This places the infant at greater risk for life threatening hemorrhage and thrombosis. Managing anticoagulation in these infants is extremely challenging and needs the expertise of a physician with a thorough knowledge of the intricacies of developmental hemostasis and limitations of the current laboratory techniques available to manage anticoagulation. This article provides a brief overview of the developing hemostatic system of the neonate and the challenges associated with managing anticoagulation in this vulnerable population of patients.